Implementasi Metode Role Play dalam Pembelajaran Fiqih Kelas XII di SMK Muhammadiyah 1 Sragen - Ilham Hidayat; Nurul Latifatul Inayati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
: This study aims to describe the application and identify the obstacles faced by the Role Play method carried out by grade XII students in the fiqh subject of chapter Initiation of Corpses at SMK Muhammadiyah 1 Sragen. This study uses a type of qualitative descriptive research with phenomenological determinism, data collection techniques through interviews, observations, and documentation. The analysis technique applied in the study consists of three streams of activities that occur simultaneously, namely data reduction, data presentation, and conclusion drawn. The results of the study show that the application of the role play method requires the active participation of students, starting from preparing tools, dividing roles to carrying out tasks such as shrouding and praying the body, which is carried out without the use of mannequins. The entire series of role plays are supervised by teachers to be in accordance with Islamic law. Teachers provide direction, correct mistakes, and evaluate learning outcomes to ensure the success of this method. In addition, this activity also provides hands-on experience that develops students' social skills, such as cooperation, responsibility, and the courage to express opinions. However, the study also noted several obstacles, such as students' lack of understanding of their respective roles and their inability to memorize the required prayer readings.